Preinkubator jako instrument rozwoju mikroprzedsiębiorstw w Polsce - Jankiewicz, Sławomir (Pre-incubator as an Instrument of Micro Enterprises Development in Poland, 2008)
One of the primary objectives of the economic policy in Poland is to generate a strong GDP growth rate. In order to maintain a long-term economic growth, it is necessary not only to secure capital for investments and introduce appropriate legal regulations. Another prerequisite is to prepare the society for challenges underlying the "informational revolution". In case of students, it has to be said that the knowledge they gained in the course of their studies may not be sufficient to effectively manage in the current ever-changing economic environment. Nevertheless, such knowledge is a good foundation for development of entrepreneurship. Therefore, it is necessary to improve the practical skills and qualifications by promoting entrepreneurship among students. This is vital as graduates should learn how to independently operate in the market. This study provides an overview of an instrument which is to help to achieve the aforementioned objectives. The instrument comprises pre-incubators operating at school. With implementation of this project, the graduates of most peoples in the country will become more creative and prone to innovative ways of thinking, and that should make Poland more competitive.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 282-292